Application of Rational Emotive Behavior Theraphy (REBT) Group Counseling Model using Cognitive Dispute Technique to reduce Online Game addiction among Junior High School Students - Evriantara, Mohammad Alvin; Soesilo, Tritjahjo Danny (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
English: The purpose of this study was to determine the effectiveness of the application of group counseling models with REBT methods of Cognitive Dispute techniques to reduce students' online game addiction behavior. The research approach used pre-experiment (Pre-test Post-test Design). This research was conducted at Satya Wacana Salatiga Christian Junior High School in the even semester of the 2023/2024 academic year. The research sample amounted to 6 students who had a problem, namely online game addiction. Data collection was carried out from the results of the pre-test and post-test in the form of questioners. Data analysis using non-parametric statistical testing. The results showed that this intervention was effective in reducing the level of online game addiction. Before the intervention, the majority of students were in the high or very high addiction category, but after counseling, the majority of students switched to the low and very low categories Indonesia: Tujuan penelitian ini untuk mengetahui efektifitas Penerapan model konseling kelompok dengan metode REBT teknik Dispute Kognitif untuk mengurangi perilaku kecanduan game online peserta didik. Pendekatan penelitian menggunakan pre-eksperimen (Pre-test Post-test Design). Penelitian ini dilaksanakan di SMP Kristen Satya Wacana Salatiga pada semester genap tahun Pelajaran 2023/2024. Sample penelitian berjumlah 6 peserta didik yang memiliki permasalahan yaitu kecanduan game online. Pengumpulan data yang dilakukan dari hasil pre-test dan post-test berupa questioner. Analisis data menggunakan pengujian statistik non parametrik. Hasil penelitian menunjukkan bahwa intervensi ini efektif dalam menurunkan tingkat kecanduan game online. Sebelum intervensi, mayoritas siswa berada dalam kategori kecanduan tinggi atau sangat tinggi, namun setelah diberikan konseling, mayoritas siswa beralih ke kategori rendah dan sangat rendah.